Ascorbic acid supplementation does not alter oxidative stress markers in healthy volunteers engaged in a supervised exercise program - Piyawan Bunpo (2018)
© 2016, National Research Council of Canada. All rights reserved. The purpose of this study was to investigate the impact of ascorbic acid (AA) consumption on the oxidative stress status of untrained volunteers participating in a supervised exercise program. The study included 46 young adults (average age, 23.5 ± 0.59 years; 37 females, 9 males) who remained sedentary (n = 16) or participated in 30 min of outdoor aerobic running (n = 30) at an intensity corresponding to 65%-75% of maximum heart rate for 3 times per week for 12 weeks. Exercised subjects were randomly assigned to an exercise group without AA supplementation (control; n = 10) or received either 250 mg (n = 10) or 500 mg (n = 10) of AA supplementation previous to each exercise session. Blood samples were taken on day 0 and day 84 to evaluate metabolic profiles and antioxidant status. Sedentary subjects underwent in a single bout of aerobic running to determine total antioxidant status (TAS) and malondiadehyde (MDA) at pre- and postexercise with or without AA supplementation. No significant change in TAS was observed. Plasma MDA significantly increased at postexercise (P < 0.05), and AA supplementation decreased MDA level significantly (P < 0.05). After 3 months of exercise, there was no significant change in blood glucose, lipid profile, MDA, TAS, superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase activities amongst groups. Supplementation of AA was associated with minor and inconsistent reductions in SOD, GPx, and catalase activities (P < 0.05). These findings indicate that pre-exercise supplementation of ascorbic acid does not alter oxidative stress markers in the plasma and erythrocytes of young adults engaged in a supervised exercise program.